2020
DOI: 10.3390/cancers12092372
|View full text |Cite
|
Sign up to set email alerts
|

Role of the CXCR4-LASP1 Axis in the Stabilization of Snail1 in Triple-Negative Breast Cancer

Abstract: The CXCL12-CXCR4 axis plays a vital role in many steps of breast cancer metastasis, but the molecular mechanisms have not been fully elucidated. We previously reported that activation of CXCR4 by CXCL12 promotes the nuclear localization of LASP1 (LIM and SH3 protein 1). The nuclear LASP1 then interacts with Snail1 in triple-negative breast cancer (TNBC) cell lines. In this study, we report that the nuclear accumulation and retention of Snail1 was dependent on an increase in nuclear LASP1 levels driven by activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 71 publications
(106 reference statements)
0
15
0
Order By: Relevance
“…These data suggest that the effect of triptonide on Snail1 expression may be limited only in the in vitro produced triptonide-resistant HCC1806 cell line, but is uncommon in TNBC cell lines. Of note, overexpression of the transcription factor Snail drives overexpression of various oncogenic and metastatic genes, activates multiple tumorigenic signaling pathways, and promotes EMT, tumorigenesis, cancer metastasis, and drug resistance [42][43][44][45][46][47][48][49][50][51]. Therefore, up-regulation of Snail1 should not be good idea for cancer therapy; instead, suppression of Snail1 should be a sensible strategy for treatment of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that the effect of triptonide on Snail1 expression may be limited only in the in vitro produced triptonide-resistant HCC1806 cell line, but is uncommon in TNBC cell lines. Of note, overexpression of the transcription factor Snail drives overexpression of various oncogenic and metastatic genes, activates multiple tumorigenic signaling pathways, and promotes EMT, tumorigenesis, cancer metastasis, and drug resistance [42][43][44][45][46][47][48][49][50][51]. Therefore, up-regulation of Snail1 should not be good idea for cancer therapy; instead, suppression of Snail1 should be a sensible strategy for treatment of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Gao B., et al reported that triptonide inhibits TNBC cell tumorigenesis via downregulation of several cancer stem cell-associated genes, up-regulation of Snail1 expression, and induction of a Snail1-associated feedback mechanism for triptonide resistance [37]. Of note, it is wellknown that Smail1 is aberrantly overexpressed in various types of malignant tumors including TNBC [38][39][40][41], overexpression of Snail triggers EMT [40,[42][43][44][45], carcinogenesis [46][47][48][49], and drug resistance [50,51], and is closely associated with poor prognosis in cancer patients [38,41,44,45,48,49]. Accordingly, inhibition of Snail1 in cancer has become a new strategy for developing cancer therapeutics [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…• The CXCR4-LASP1 axis enhances the stability of nuclear Snail1, to promote invasion of TNBC cells [133]. • CXCL12/CXCR4 promotes invasion of ovarian cancer cells by means of suppressing ARHGAP10 expression [134].…”
Section: Cxcl12 Cxcr4mentioning
confidence: 99%
“…A total of 2023 cancer patients from 18 included studies concerning LASP1 were included in this study [9][10][11][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The sample size in these studies ranged from 32 to 216.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The included studies were performed in Asia, Europe and North America, and majority of these studies were conducted in China. Among the 18 eligible studies, 16 studies reported OS [9,11,[15][16][17][18][19][20][21][22][23][24][25][26][27]29], 2 studies reported RFS [20,28], and 13 studies reported clinicopathological parameters [9-11, 15-20, 22, 23, 27, 29]. The included articles varied in their detection regions of LASP1 expression and the cut-off value for LASP1 positive, which might have an effect on the positive rate of LASP1 overexpression.…”
Section: Study Characteristicsmentioning
confidence: 99%